Morphological and molecular characterization of two species of nematodes (Oxyuridomorpha: Thelastomatoidea: Protrelloididae, Thelastomatidae) parasitic in the cockroach Blaberus discoidalis Serville (Blattaria: Blaberidae) from Cuba - Morffe, Jans; García, Nayla; Véliz, Laura; Hasegawa, Koichi; Carreno, Ramon A. (Zootaxa, 2022)
Protrelleta floridana Chitwood, 1932 and Cranifera cranifera (Chitwood, 1932) (Oxyuridomorpha: Thelastomatoidea: Protrelloididae, Thelastomatidae) are recorded for the first time in Cuba. These nematodes were found to parasitize the cockroach Blaberus discoidalis Serville (Blattaria: Blaberidae), constituting a new host record for them. Both species are redescribed with the aid of scanning electron microscopy and the arrangement of the copulatory papillae of the males of P. floridana is amended. The present specimens coincide in their morphology and most of the measurements with the type populations from USA and the records from Costa Rica, with only minor differences. The molecular phylogeny was inferred by mean of the D2-D3 domain of the 28S rDNA and the Cuban P. floridana and C. cranifera form monophyletic clades with sequences of both taxa from Costa Rica as well as a sequence of C. cranifera from Russia. In the case of C. cranifera its phylogeny and that of its blaberid hosts reveal coevolutionary relationships.